'The Last Shot'—the shared and distinct brain regions involved in processing unexpectedness of success and failure in the context of social cooperation. Issue 1 (18th August 2022) - Li, Peng; Wang, Jing; Liu, Yi
Abstract: Individual success and failure in social cooperation matter not only to oneself but also to teammates. However, the common and distinct neural activities underlying salient success and failure in social cooperation are unclear. In this functional magnetic resonance imaging (fMRI) study, participants in the social group (Experiment one) cooperated with two human beings during a dice-gambling task, whereas those in the nonsocial group (Experiment two) cooperated with two computers. The social group reported more pride in success and more guilt in failure. The fMRI results in Experiment one demonstrate that left temporoparietal junction (LTPJ) activation increased exclusively with linearly changing unexpected success, whereas increasing anterior cingulate cortex (ACC) activation was only coupled with increasing unexpectedness of failure. Moreover, the dorsal medial prefrontal cortex (dMPFC) and left anterior insula were recruited in both success and failure feedback conditions. Dynamic causality model analysis suggested that the dMPFC first received information from the LTPJ and ACC separately and then returned information to these regions. The between-experiment comparison showed more dMPFC activity in social vs nonsocial contexts irrespective of success and failure feedback. Our findings shed light on the common and distinct neural substrates involved in processing success and failure feedback in social cooperation.